Considering New Perspectives in ELT in Colombia: From EFL to ELF - Diego Fernando Macías (Asociación Colombiana de Profesores de Ingles, 2010)
This article aims to explore the characteristics of English as a lingua franca (ELF) as an alternative to English Language Teaching (ELT) in Colombia. It focuses initially on the role played by English in the country and on what the English as a Foreign Language (EFL) model has offered the teaching of English. This is followed by considerations regarding aspects such as teachers, methodologies, teaching materials and culture from the viewpoint of ELF. In short, the author suggests a more international dimension to the teaching of English in Colombia in an attempt to reduce the role played by hegemonic dominant Inner Circle (Kachru, 1992) varieties in ELT in Colombia.